Patient preferences for treatment of advanced melanoma: impact of comorbidities - Weilandt, Juliane; Diehl, Katharina; Schaarschmidt, Marthe-Lisa; Kiecker, Felix; Sasama, Bianca; Pronk, Melanie; Ohletz, Jan; Koennecke, Andreas; Mueller, Verena; Utikal, Jochen; Hillen, Uwe; Harth, Wolfgang; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
Background and objectives: Choice of treatment for advanced melanoma is crucially influenced by comorbidities and patient preferences. Our study aimed to investigate the impact of comorbidities on preferences. Patients and methods: 150 patients with melanoma stage IIC–IV completed a discrete choice experiment to determine preferences for outcome (overall response rate [ORR], 2-year survival, progression-free survival [PFS], time to response [TTR], kind of adverse events [AE], AE-related treatment discontinuation) and process attributes (frequency and route of administration [RoA], frequency of consultations) of systemic melanoma treatments. The impact of comorbidities was assessed by analysis of variance and multivariate regression. Results: Participants with hypertension and other cardiovascular diseases attached significantly greater importance to TTR and RoA than others. Respondents with arthropathy cared more about TTR (β = 0.179, P = 0.047) and RoA, but less about ORR (β = –0.209, P = 0.021). Individuals with diabetes considered AE (β = 0.185, P = 0.039) and frequency of consultations more essential, but ORR less relevant. Those with other malignancies were particularly worried about treatment discontinuation (β = 0.219, P = 0.008), but less about ORR (β = –0.202, P = 0.015). Participants with depression focused more on PFS (β = 0.201, P = 0.025) and less on TTR (β = –0.201, P = 0.023) and RoA (β = –0.167, P = 0.050). Conclusions: Treatment preferences of melanoma patients vary significantly dependent on comorbidities.
CRIS-Team Scopus Importer:2021-12-06